Photothermal Therapy Based on CuS Nanoparticles for Alleviating Arterial Restenosis Induced by Mechanical Injury of Endovascular Treatment - Wu, Xiaoyu; Liu, Kun; Huang, Qun; Zhang, Qin; Yang, Xinrui; Liu, Xiaobing; Wang, Ruihua (Frontiers in Materials, 2021)
CuS nanoparticles (NPs) as an effective near infrared (NIR) absorption agent have been widely applied in the photothermal therapy (PTT) of cancer. However, little is known about the application of CuS NPs based PTT in alleviating arterial inflammation and restenosis, which affects the long-term prognosis of endovascular treatment. In this study, CuS NPs were synthesized and used as PTT nanoplatform for ameliorating arterial inflammation induced by mechanical injury of endovascular treatment. The macrophages possessed powerful phagocytosis toward CuS NPs as evidenced by intracellular transmission electron microscopic imaging. As illustrated from CCK-8 assay and calcein AM/PI staining, an efficient depletion of macrophages by CuS NPs coculture combined with the irradiation with a 915 nm NIR laser was achieved. The endarterium injury/inflammation model was established by insertion of a 29G needle (BD Insulin Syringe Ultra-Fine®) to the left common carotid artery of apolipoprotein E knockout mouse to mimic endarterium damage after endovascular treatment. Local injection of CuS NPs around the left common carotid artery followed by irradiation with a 915 nm INR laser significantly depleted infiltrated macrophages and alleviates arterial stenosis. This work emphasizes the role of CuS NPs as PTT agent in post-injury remodeling of arterial wall and provides an attractive target-macrophage-that can be depleted to alleviate arterial stenosis.